Bioadhesive HPMC Gel Containing Gelatin Nanoparticles for Intravaginal Delivery of Tenofovir - Sreejan Mannaa, Uppadi Swathi Lakshmia, Manasa Racharlaa, Pratyusha Sinhab, Lakshmi Kanta Kanthala, S. P. N. Kumara (Journal of Applied Pharmaceutical Science, 2016)
The aim of the present study is to formulate tenofovir loaded gelatin nanoparticles by two step desolvation method for targeted release of drug by varying the concentration of polymer and cross-linking agent. Entrapment efficiency for all the formulations was found to be within 67.32 ± 1.24 % to 92.11 ± 1.13 %. Average particle size of different tenofovir loaded gelatin nanoparticle formulations was found within the range of 294.9 - 445.3 nm. In-vitro drug release study for glutaraldehyde cross linked gelatin nanoparticles were found between 67.09 % ± 1.423 – 82.41 % ± 1.874 after 8 h of dissolution. F5 (850 mg gelatin, 0.2 ml glutaraldehyde) was considered as the best formulation based on the entrapment efficiency and drug release from nanoparticle core. Kinetics study was performed for all the formulations and best fit model for drug release was determined depending on R squared values. HPMC K15M was used as a bioadhesive polymer as well as a gelling agent. Three different gel formulations were prepared by varying concentration of HPMC K15M and incorporated with the best formulation, F5. Membrane permeation and bio-adhesion study revealed F5B gel (5% HPMC K15M) as an optimum formulation with suitable bioadhesive strength and membrane permeability.
Keywords: Tenofovir, gelatin, glutaraldehyde, bioadhesive, HPMC K15M.